Family structure diversity: Views from rural community leaders and implications for youth engagement. Issue 2 (14th March 2020) - Anakwe, Adaobi; Majee, Wilson; Keller, Kimberly J. M.; Jooste, Karien
ABSTRACT: As family structures continue to evolve, understanding how communities perceive these changes and influences on youth engagement is important. This study examined community leaders' perceptions of rural youth engagement as influenced by family structural changes. Fifteen rural community leaders were interviewed, and data were analyzed thematically. Three major themes emerged: familial influence on youth development, parents' beliefs on structurally diverse homes, and community as a resource for youth engagement . Findings suggest that community leaders (a) perceived families as the primary influence in youth development (b) endorsed the view that non-nuclear families are broken, and (c) felt youth emerging from these family types are less motivated to engage in community life than their counterparts from nuclear family households. Community leaders predominantly assumed that family structure diversity was the strongest determinant of youth engagement within their community, without accounting for qualitative differences in resources provided to match youth interest.